1, 4-Diketo-pyrrolo[3, 4-c]pyrroles (DPPs) based insoluble polymer films with lactam hydrogens as renewable fluoride anion chemosensor. (1st August 2018) - Zhang, Haichang; Yang, Kun; Chen, Chao; Wang, Yanhui; Zhang, Zhenzhen; Tang, Liangliang; Sun, Qikun; Xue, Shanfeng; Yang, Wenjun
Abstract: Manipulating the sub-units of conjugated co-polymers was a convenient and promising strategy for developing novel functional materials. Here a soluble alternating copolymer (P-Boc) consisted of 9, 9-dialkylfluorene and 1, 4-diketo-2, 5-di( t -butoxycarbonyl)-3, 6-diphenyl-pyrrolo[3, 4- c ]-pyrrole was designed and synthesized. Heating the spin-coated P-Boc film could afford an insoluble polymer film (P-2H) with multiple lactam hydrogen units by the removal of the t -butoxycarbonyl groups. Unlike the small molecules with lactam hydrogen, the P-2H film was insoluble and exhibited the remarkable naked-eye visible color change and a new long-wavelength absorption band in the fluoride anion-containing organic solution. The naked-eye visible and spectroscopic detection limits for fluoride anion were ∼10 −6 and ∼10 −8  M, respectively. Moreover, the fluoride anions bonded with P-2H film could be easily removed by immersing in acidic solutions, and the resulting P-2H film could again probe fluoride anion. Energy dispersive X-ray spectroscopy analysis indicated that most lactam units in P-2H film could bond fluoride anions and the bonded fluoride anions could be removed quantitatively. These results demonstrated that P-2H was not only an efficient and renewable fluoride anion chemosensor but also might become a promising fluoride anion extractor. Graphical abstract: Preparation, characterization, and application of DPP-based insoluble polymer film with lactam hydrogens through thermal annealing its solution-processed precursor polymer film for fluoride anion sensors; the fluoride anion detection limitation as low as 10 −8  M. Image 1 Highlights: DPP-based insoluble polymer film (P-2H) with lactam hydrogens was prepared upon heating t -Boc functionalized P-Boc film. P-2H film exhibited remarkable naked-eye visible color change in the fluoride anion-containing organic solution. The spectroscopic detection limits of P-2H film for fluoride anion were 10 −8  M. The sensing ability of P-2H for fluoride anion can be recovered, making it promising fluoride anion sensor and extractor.